Coronary Assessment and Revascularization Before Transcutaneous Aortic Valve Implantation: An Update on Current Knowledge - Sabbah, Muhammad; Engstrøm, Thomas; De Backer, Ole; Søndergaard, Lars; Lønborg, Jacob (Frontiers in Cardiovascular Medicine, 2021)
Transcutaneous aortic valve implantation (TAVI) has led to a paradigm shift in the treatment of severe aortic stenosis (AS) in the elderly and is expanding to still younger and lower-risk patients with severe AS as an alternative to surgical aortic valve replacement (SAVR). While the role of coronary artery bypass grafting (CABG) with SAVR is well documented, the analog of percutaneous coronary intervention (PCI) with TAVI is less so. The aim of this review is to provide an overview of the important challenges in treating severe AS and co-existing coronary artery disease (CAD) in patients planned for TAVI.